THE CORRELATION BETWEEN LISTENING ENGLISH SONGS HABIT WITH SPEAKING ACHIEVEMENT OF THE TENTH GRADE STUDENTS OF SMK SMSR UBUD IN ACADEMIC YEAR 2020/2021 - Ni Komang Sinta; Ni Made Wersi Murtini; Dewa Gede Agung Gana Kumara (Academic Journal on English Studies (AJOES), 2021)
In conveying ideas, speaking skills are very important to be honed. That way we candeliver the message that we will create through speaking, and make it easier for people whoneed information to understand about the meaning. This study aims at finding out the correlationbetween students’ listening English songs habit with speaking achievement of the tenth grade studentsof SMK SMSR Ubud in academic year 2020/2021. In taking the research, simple random sampling wasapplied. The design was ex-post facto correlational research design. In collecting the data of thisresearch, the writer used two instruments which were listening English songs habit questionnaireconsisted of 30 items distributed through Google Form and monologue speaking test distributedthrough Google Zoom. The data was analyzed by using Pearson Product Moment Correlation in IBMSPSS Statistics. Acording to the result of the analysis and statistical calculation, it is found that r was0.957. It shows that there is significant correlation between listening English songs habit with speakingachievement of the tenth grade students of SMK SMSR Ubud in academic year 2020/2021. It liesbetween 0.800 – 1.00 which is in very high level.